Lipopolysaccharide-Deficient Brucella Variants Arise Spontaneously during Infection - Turse, Joshua E.; Pei, Jianwu; Ficht, Thomas A. (Frontiers in Microbiology, 2011)
Lipopolysaccharide-deficient mutants of smooth Brucella species (rough mutants) have been shown to arise spontaneously in culture. However, in situ analysis of Brucella infected macrophages using antibody directed against O-polysaccharide suggested a loss of reactivity of Brucella consistent with the appearance of rough organisms, and a potential contribution to infection. The experiments reported describe the direct recovery of Brucella from macrophages infected in vitro and from the spleens of infected mice at a frequency similar to that described in vitro, suggesting that Brucella dissociation is not simply an in vitro artifact. The frequency of appearance of spontaneous rough organisms deficient in O-polysaccharide expression measured in vitro is approximately 2-3 logs higher than the appearance of mutation to antibiotic resistance, purine auxotrophy or reversion of erythritol sensitive ∆eryC mutants to tolerance. Genetic trans-complementation using a plasmid-based expression of Brucella manBA successfully restored O-polysaccharide expression in only one third of O-polysaccharide deficient spontaneous mutants. Suggesting that the appearance of rough mutants is caused by mutation at more than one locus. In addition, Sanger sequencing of the manBA structural genes detected multiple sequence changes that may explain the observed phenotypic differences. The presence of O-polysaccharide resulted in macrophage and neutrophil infiltration into the peritoneal cavity and systemic distribution of the organism. In contrast, rough organisms are controlled by resident macrophages or by extracellular killing mechanisms and rapidly cleared from this compartment consistent with the inability to cause disease. Loss of O-polysaccharide expression appears to be stochastic giving rise to organisms with biological properties distinct from the parental smooth organism during the course of infection.